Low-operating voltage-based piezoelectric ultrasonic actuator for tactile system applications. Issue 1 (10th December 2021) - Mukhopadhyay, Shalini; Kumar, Jayendra; Behera, Basudeba
Abstract: This article presents the design and analysis of a piezoelectric-based ultrasonic actuator to be used for tactile system applications. The device made of four pieces of piezoelectric material arranged in alternate way to complete the actuator structure. When the voltages are applied on the device, and at a resonant operating frequency, two vibration modes are simultaneously activated, the first longitudinal mode ( L 1 ) and the second bending mode ( B 2 ). The actuator size is tiny and able to drive the external load with stable and low-input voltage. The proposed actuator is suited for tactile feedback device, as well as feasible for low-input applications for prolonged usage. From the study, it is observed that the maximum output force at the voltage of 50 V is 1.6 N for the proposed structure while the optimum force is 1 N. Its small dimension, 20.1 × 2 × 0.75 mm and low-input voltage of 50 V makes it portable and easy to fabricate into small and precise devices.